2011
DOI: 10.1016/j.ajhg.2011.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing Identifies Truncating Mutations in Human SERPINF1 in Autosomal-Recessive Osteogenesis Imperfecta

Abstract: Osteogenesis imperfecta (OI) is a heterogeneous genetic disorder characterized by bone fragility and susceptibility to fractures after minimal trauma. After mutations in all known OI genes had been excluded by Sanger sequencing, we applied next-generation sequencing to analyze the exome of a single individual who has a severe form of the disease and whose parents are second cousins. A total of 26,922 variations from the human reference genome sequence were subjected to several filtering steps. In addition, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
236
1
16

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 325 publications
(269 citation statements)
references
References 59 publications
11
236
1
16
Order By: Relevance
“…Osteogenesis imperfecta type VI is caused by reces sive null mutations in SERPINF1, which encodes pigment epithelium derived factor (PEDF). PEDF is an anti angiogenic factor that also interacts with recep tor activator of nuclear factor κβ ligand (RANKL; also known as TNFSF11) pathway, thereby increasing the activity of osteoclasts [83][84][85] (FIG. 4a).…”
Section: Box 1 | Classification Of Osteogenesis Imperfectamentioning
confidence: 99%
“…Osteogenesis imperfecta type VI is caused by reces sive null mutations in SERPINF1, which encodes pigment epithelium derived factor (PEDF). PEDF is an anti angiogenic factor that also interacts with recep tor activator of nuclear factor κβ ligand (RANKL; also known as TNFSF11) pathway, thereby increasing the activity of osteoclasts [83][84][85] (FIG. 4a).…”
Section: Box 1 | Classification Of Osteogenesis Imperfectamentioning
confidence: 99%
“…After this, typically between 150 and 500 private non-synonymous or splicesite variants are prioritized as potential pathogenic variants (see Figures 1 and 2). 4,[28][29][30][31][32][33][34] It is important to emphasize that prioritization may discard the pathogenic variant. A variant that is present at low frequency in a heterozygous state in the normal population may be removed even though it causes disease if present in a homozygous state.…”
Section: Disease Gene Identification Strategies For Exome Sequencingmentioning
confidence: 99%
“…Homozygous variants can therefore be prioritized by their presence in large homozygous regions of the patient's genome. These regions can be identified by SNP microarrays and used during the prioritization process, 35 but Becker et al 31 recently showed that exome data itself may contain sufficient numbers of informative SNPs to allow reliable homozygosity mapping. In this study, 17 of the 318 private non-synonymous variants observed in the index patient were autosomal homozygous variants, but only three were located in large homozygous regions and the causative mutation was located in the largest of these three.…”
Section: Affecting Protein Sequencementioning
confidence: 99%
See 1 more Smart Citation
“…SERPINF1 mutations have been shown to cause premature termination codons and subsequent loss of PEDF expression [46]. How this leads to under mineralized bone in extracellular matrix has yet to be explained.…”
Section: Autosomal Recessive Oimentioning
confidence: 99%